Rethinking the Validity of Online Church During the COVID-19 Lockdown Period - Manotar Tampubolon (Indonesian Journal of Religion and Society, 2023)
The COVID-19 pandemic has changed the scope of the world, and various stakeholders have used technological advancements around the world. Fear of death and health emergencies have brought people closer to religion. However, social and other limitations have made it hard for people to keep their religious duties. This study examines the use of technology and the online church for Christian services during the COVID-19 lockdown period, which is not in accordance with the concept of congregation. The author discusses the validity of the use of technology and online church by Christians and how it impacts traditional worship services from biblical and theological perspectives. Research Findings show the high attendance after the change from traditional worship services to the use of technology and online church. The data used in this study is secondary data that was found through desk research and reliable sources. The research findings indicate big effects on all parts of society and religion, which should not be a surprise. The epidemic has changed religious practices from traditional to online church and contradicts biblical injunctions. Most religions, including Christian ones, put a lot of emphasis on the importance of community. It has been found that online churches have become popular in the proposed areas, and the technology provides a better opportunity for Christians in Nigeria, the Balkans, and Indonesia to carry out their religious obligations by following lockdown restrictions